دور التعليم الالكتروني في تحقيق أهداف التعليم عن بعد في كلية العلوم الاجتماعية والتطبيقية -جامعة عدن- تصور مقترح - ماسة, محفوظ (University of Eloued جامعة الوادي, 2021)
ملخص: هدفت الدراسة الحالية إلى الكشف عن دور التعليم الالكتروني كتقنية حديثة في تحقيق أهداف التعليم عن بعد في كلية العلوم الاجتماعية والتطبيقية بجامعة عدن. وقد قدمت الدراسة عرض لتجارب بعض الكليات والمراكز في الجامعات اليمنية في مجال التعليم عن بعد ومدى توظيف التعليم الالكتروني لتحقيق أهدافها. كما أسهمت الدراسة بوضع تصور مقترح لتوظيف وتفعيل التعليم الالكتروني في برامج التعليم عن بعد بكلية العلوم الاجتماعية والتطبيقية - جامعة عدن -. توصلت الدراسة إلى أن التعليم الالكتروني في كلية العلوم الاجتماعية والتطبيقية بجامعة عدن لم يتم تطبيقه بالرغم من أنها سعت جاهدة إلى إدخاله في برامج التعليم عن بعد وذلك لما يوفره من إمكانيــة كبيــرة جــداً فــي إعطــاء فرصــة التعلــيم إلــى العديــد مــن فئــات المجتمع لاسيما تلك الفئات التي فاتتها فرصة الحصول على التعليم بغض النظر عن الأسباب, في الوقت الذي نجد فيه عدد من الجامعات اليمنية الأهلية مثل كلية التعليم المفتوح بجامعة العلوم والتكنولوجيا, كلية التعليم المفتوح بجامعة المستقبل ومركز التعليم عن بعد بجامعة الأندلس قد سبقتها في توفير بنية تعليمية تحتية وتقنية بما يتناسب ونمط التعليم الإلكتروني وصيغة التعليم عن بعد. The current study aims to uncover the role of e-learning as a modern technology in achieving the objectives of distance education in the Faculty of Social and Applied Sciences, Aden University. It presents the experiences of some colleges and centers in Yemeni universities in the area of distance education and the extent e-learning is employed to achieve their goals. The study also contributes to developing a proposed scenario for employing and activating electronic education in distance education programs at the Faculty of Social and Applied Sciences, Aden University. The study concludes that e-learning in the College of Social and Applied Sciences, Aden University, has not been applied even though the faculty has strived to include it in distance education programs because it provides a very great potential for giving education to many groups of society, especially those who missed their opportunity to have access to education regardless of the reasons, at a time when we find a number of private Yemeni universities such as the Faculty of Open Education, Science and Technology University, the Faculty of Open Education at Future University and the Center for Distance Education at Al-Andalus University have preceded it in providing an educational structure, infrastructure and technology that commensurate with the type of e-learning and distance education format.
مقال
Keywords: التعليم الالكتروني ; التعليم عن بعد ; التصور المقترح.